Perancangan Antarmuka Pengguna Website Responsif Mobile Byboot Menggunakan Metode Design Thinking - Naufal Zulfikar Priambodo; Satrio Hadi Wijoyo; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Byboot is a Micro, Small and Medium Enterprise (MSME) in Jombang Regency which is engaged in fashion, specifically selling various needs for sandals and women's shoes. Byboot wanted to expand its business reach and wanted an e-commerce website. This website will be used to assist transactions between Byboot and its customers so that the transaction process runs effectively and efficiently. Based on these problems, the researcher provides a solution for designing the user interface of an e-commerce website that will be made in the form of a high-fidelity prototype. This design will make it easier for Byboot and consumers to make buying and selling transactions that they will do. The process of designing this system will use the design thinking method in which there are five stages in the process, namely empathize, define, ideate, prototype and test. The testing process will include usability testing, user interviews, and a system usability scale (SUS) questionnaire. From the test results with the system usability scale questionnaire, it was obtained a value of 77 for the consumer system and a value of 75.5 for the stakeholder system. The results of the two systems are included in the high acceptability level, with a grade scale C, and also an adjective rating of Good.